DAMPAK KONFLIK TERHADAP PEREKONOMIAN MASYARAKAT DI NEGERI MAMALA DAN MORELLA - Farid Naya (IAIN Ambon, 2018)
This study aims to find answers to two research queation. Firt, why the conflik continue to occur at both the community? Second, how the conflikt persistent impact on the economy of these societies? This study uses qualitative research methods (qualitavie research method) approach verstehen or understanding to explore from the inside (Inside View) value or meaning derived from the subject of research by individuals and the dynamics of conflict in the country Mamala and Morella, as well as how the economic impacts both communities in both countries. Data obtained through observation, interview and documentation. Data analysis begins with making abstraction, making categorization, coding, data validity checking, and interpret data and draw conclusion. The results showed that, first, the conflict is a consequence arising from social interaction with a social structure that is built in the community both countries. The second aspect of the historicity of the country to be one trigger their intensity conflict. Cleim legitimacy of customary dyeing masyaramat awareness of both countries. Second, conflicts which continue to experience the intensity, has a negative impact on both the community. One is the level of the costliness of the local community product sales. Start of production of fish by fishermen arrests in both societies.